The Influence of Personality and Motivation on Teacher's Job Performance - Ridwan Nasution; Zulkifli Musannip Efendi Siregar; Rachmat Rachmat; Kurnia Tika Sari (Garuda Prestasi Nusantara Consulting, 2022)
This study aims to determine the effect of personality and motivation on teacher job performance at SMA Negeri 1 Panai Tengah, Labuhanbatu Regency. The population of this study were teachers at SMA Negeri 1 Panai Tengah, Labuhanbatu Regency, with a total of 30 respondents. The sample used is as many as 30 respondents. The data analysis technique used was path analysis with the help of Amos Software Version 23. The results showed that there was a positive and significant influence between personality and teacher work motivation. Teacher work motivation has a positive and significant effect on teacher work performance. Meanwhile, personality does not have a significant effect on teacher work performance. Keywords : Personality, Motivation, Job Performance